Patients with hypertrophic obstructive cardiomyopathy after alcohol septal ablation have favorable long-term outcome irrespective of their genetic background - Bonaventura, Jiří; Norambuena, Patricia; Votýpka, Pavel; Hnátová, Hana; Adlová, Radka; Macek, Milan; Veselka, Josef (Cardiovascular diagnosis and therapy, 2020)
BACKGROUND: The genetic background of patients with hypertrophic cardiomyopathy (HCM) treated with alcohol septal ablation (ASA) and its relationship to the outcomes are not known. We aimed to investigate whether the outcome of genotype positive (G+) patients differs from genotype negative (G-) patients treated with ASA. METHODS: We included 129 HCM patients (mean age 54±13 years) treated with ASA in a tertiary cardiovascular center and performed next generation sequencing (NGS) based genomic testing. All patients were followed-up three months after the procedure and yearly thereafter. RESULTS: A total of 30 (23%) HCM patients were G+ patients. At the 3-months follow-up, both groups of patients had similar left ventricular outflow tract PG (16.9±15.7 mmHg in G+ vs. 16.3±18.8 mmHg in G-, P=0.73) and symptoms (follow-up NYHA class 1.40±0.62 vs. 1.37±0.53, P=0.99, follow-up CCS class 0.23±0.52 vs. 0.36±0.65, P=0.36). The independent predictors of all-cause mortality were baseline interventricular septum (IVS) thickness (HR 1.12, 95% CI: 1.00-1.26, P=0.049) and age at the time of ASA (HR 1.11, 95% CI: 1.06-1.17, P<0.01). The adjusted all-cause mortality rate did not differ significantly between G+ and G- patients (P=0.52). The adjusted combined mortality event rate did not differ between both groups (P=0.78). CONCLUSIONS: Despite more severe phenotype in G+ HCM patients, ASA is an equally effective treatment for LVOTO in G+ patients as it is for treating LVOTO in G- patients. The long-term outcome after ASA is similar in G+ and G- patients.
Keywords: Cardiomyopathy; alcohol septal ablation (ASA); genetics; hypertrophic cardiomyopathy (HCM); hypertrophic obstructive cardiomyopathy